2016
DOI: 10.1021/jacs.6b11140
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit[7]uril–Tetramethylrhodamine Conjugate for Direct Sensing and Cellular Imaging

Abstract: This paper describes the design and synthesis of a conjugate (Q7R) comprising the synthetic host cucurbit[7]uril (Q7) linked to the fluorescent dye tetramethylrhodamine (TMR), and the characterization of its optical and guest-binding properties as well as its cellular uptake. Q7R was synthesized in two steps from monofunctionalized azidobutyl-Q7 and NHS-activated TMR. The fluorescence of Q7R is quenched upon guest binding, and this observable was used to determine equilibrium dissociation constant (K) values. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 39 publications
1
85
0
1
Order By: Relevance
“…[22] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 including those using strong light sources and lasers, can be established using CBn macrocycles. [34,63,64,65,66,67,68,69,70,71] Da Silva, Hubbard and co-workers demonstrated in vivo use of CB7 in tilapia fish; the encapsulation of odorants such as cadaverine by CB7 tuned down the response of the olfactory receptors. [34,63,64,65,66,67,68,69,70,71] Da Silva, Hubbard and co-workers demonstrated in vivo use of CB7 in tilapia fish; the encapsulation of odorants such as cadaverine by CB7 tuned down the response of the olfactory receptors.…”
Section: Analytementioning
confidence: 99%
See 1 more Smart Citation
“…[22] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 including those using strong light sources and lasers, can be established using CBn macrocycles. [34,63,64,65,66,67,68,69,70,71] Da Silva, Hubbard and co-workers demonstrated in vivo use of CB7 in tilapia fish; the encapsulation of odorants such as cadaverine by CB7 tuned down the response of the olfactory receptors. [34,63,64,65,66,67,68,69,70,71] Da Silva, Hubbard and co-workers demonstrated in vivo use of CB7 in tilapia fish; the encapsulation of odorants such as cadaverine by CB7 tuned down the response of the olfactory receptors.…”
Section: Analytementioning
confidence: 99%
“…[72] (However, CBn and CBn complexes can bind to certain proteins and thereby affect some enzymatic functions, e. g., that of type II endonucleases or proteases, as was shown by the groups of Nau and Pischel.) [40,71,76,77,78,79,80,81,82,83,84,85,86] Similarly, functionalisable acyclic CBn derivatives are also available, enabling the instalment of signalling units into the formally dark/transparent cucurbiturils. [40,71,76,77,78,79,80,81,82,83,84,85,86] Similarly, functionalisable acyclic CBn derivatives are also available, enabling the instalment of signalling units into the formally dark/transparent cucurbiturils.…”
Section: Analytementioning
confidence: 99%
“…[37,38] Recent studies by several groups demonstrated the potential of applying CB[n]-mediated complexes for anticancer therapies, for example as drug carrier or sensors. [39][40][41][42] In the design of dynamic systems with on-demand changes in guest binding by stimuli-responsiveness, it is attractive to exploit CB[n] since they are selective binders while being sensitive to changes in molecular structure of the guests. [43] An early reported example is the shuttling of CB [6] along a triamine chain.…”
Section: Host-guest Chemistry Of Cucurbit[n]urilsmentioning
confidence: 99%
“…Therein, the fluorescence properties of a dye are altered when encapsulated by the host, and when a competitive binder displaces the dye from the cavity, the properties of the non-encapsulated dye are regenerated. This principle has enabled, for example, real-time monitoring of enzymatic activity [1820], the detection of membrane-transport activity [21] and membrane fusion [22], and even cellular imaging appears to be a potential future prospect [2324]. …”
Section: Introductionmentioning
confidence: 99%
“…One possibility is the utilization of monofunctionalized CBs with outer cavity-attached fluorescent dyes [22,24]. This principally allows for the modular construction of various Förster resonance energy transfer (FRET) pairs as demonstrated with a Cy3-attached CB7, or the design of self-inclusion complexes, in which an outer cavity-attached rhodamine was intramolecularly bound in the CB7 cavity.…”
Section: Introductionmentioning
confidence: 99%